An Admissible Monetary Aggregate for the United Kingdom - Belongia, Michael T.; Chrystal, K. Alec (The Review of Economics and Statistics, 1991)
This paper evaluates the performance of a monetary aggregate that is constructed from principles of economic and index number theory. Results from tests for weak separability indicate that wholesale deposits should not be aggregated with other U.K. financial assets; they currently are included, however, in broad monetary aggregates published by the Bank of England. Financial asset groupings passing the weak separability tests then were aggregated using both simple-sum and Divisia weights. In each case, the Divisia aggregates were more closely related to the growth of nominal GDP and had stable demand for money functions. Copyright 1991 by MIT Press. (This abstract was borrowed from another version of this item.)